Hubungan Antar Disiplin Belajar Dengan Hasil Belajar pada Mata Pelajaran Bahasa Indonesia Kelas V di SD - Laseri, Laseri; Wardiah, Desyy; Kuswidyanarko, Arief (Institut Teknologi Pendidikan Indonesia, 2022)
Learning discipline is obedience and adherence to written and unwritten rules in the process of behavior change so that learning discipline can affect student learning outcomes. This study aims to determine the relationship between learning discipline and student learning outcomes in Indonesian class V.B. subjects at SD Negeri 87 Palembang. This research is a correlational study because it involves two variables in which the two variables have a relationship. The population in this study were all fifth graders, totaling 92 students. Data collection techniques used are questionnaires, documentation, and tests. The data analysis technique used is the normality test using the Kolmogorov-Smirnov test, the homogeneity test using the Harley test, and hypothesis testing using the correlation test using the Pearson Product Moment formula. Based on the results of the study, obtaining the value of thecorrelation coefficient or